Pengaruh Profesionalisme Guru Pendidikan Agama Kristen Terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 1 Salak Kabupaten Pakpak Bharat Tahun Pembelajaran 2023/2024 - Rumenta Hanta Hoki Cibro; Robinhot Sihombing; Oloria Malau; Elsina Sihombing; Malani Simanungkalit (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
This research aims to determine the influence of professionalism of Christian religious education teachers on the learning motivation of class VIII students at SMP Negeri 1 Salak, Pakpak Bharat Regency for the 2023/2024 academic year. Hypothetically, there is a positive and significant influence between the Professionalism of Christian Religious Education Teachers on the Learning Motivation of Class VIII Students at SMP Negeri 1 Salak for the 2023/2024 Academic Year. The research population was 152 people and the research sample was 31 people. Data was collected using a closed questionnaire of 50 items which were compiled by research based on variable indicators in accordance with expert theory. Instrument testing was carried out on 31 Class VIII students of SMP Negeri 1 Salak who were not research respondents whose validity and reliability had been tested. The results of data analysis show that there is no positive and significant influence between the Professionalism of Christian Religious Education Teachers on the Learning Motivation of Class VIII Students of SMP Negeri 1 Salak for the 2023/2024 Academic Year with a significant test of the influence obtained by tcount < ttable of 0.24 < 1.749, thus it can be concluded that H0 is accepted and Ha is rejected.